Stability of coaxial cylindrical shells containing a rotating fluid - Bochkarev, Sergey Arkadievich; Matveenko, Valeriy Pavlovich (Computational Continuum Mechanics, 2013)
The dynamic behavior of coaxial cylindrical shells of revolution interacting with the rotating flows of a compressible fluid is studied. The flowing fluid properties are described within the framework of the potential theory. The classic shell theory is used to model elastic shells. In the numerical implementation, a semi-analytic finite element technique is applied. Numerical experiments carried out on shells with different boundary conditions and different values of the annual gap between the shells provide evidence for the existence of a subset of new qualitative regularities.